Assessment of recreational pattern of students in higher institutions of Ondo and Ekiti States, Nigeria. - EMMANUEL, Adebayo Adewunmi; AJAYI, Modupe Olayinka (2008)
Recreation is very vital for all categories of persons in the society no matter the age, social or economic status considering the stress placed upon each individual in order to make ends meet and the resultant hazard on individuals. The assumption is that Nigerian students are too encumbered with heavy academic burden such that they are too busy to recreate. This paper focuses on the recreational pattern of students in institutions of higher learning in two contiguous south-western states in Nigeria, namely Ondo and Ekiti. In particular, the study looked into the adequacy of facilities available in the institutions, the frequency of students’ participation in recreation and factors inhibiting their participation in recreational activities. In addition, students’ preference for the different forms of indoor and outdoor recreational activities and the propensity to pay for the use of recreational facilities were investigated. Fifty questionnaire copies were administered on randomly sampled students from each of the six institutions of higher learning in both states. A total of three hundred questionnaire copies were thus administered. It was discovered among other things that more students gyrate by going to parties rather than night clubs while (as a big surprise) the greatest number of students see their academic work as posing very little hindrance to their recreation and more than two-third will be willing to pay for the use of recreational facilities provided on campus if the need arises.